Semantic Analysis of Language Acquisition in Three Years Old Child - Tri Indah Rezeki; Rakhmat Wahyudin Sagala (Jurnal Serunai Bahasa Inggris, 2020)
Three years old children acquire language after their first language and it is influenced by two factors, namely physiological factors and psychological factors. Physiological factors include speech-producing organs such as mouth and brain function. Meanwhile, psychological factors include development cognitive of a child in the process of mastering his or her first language. This study was conducted to analyze the semantic analysis of language acquisition in 3 years old child. Specifically, it discussed about the errors of phonemes which were spoken by three years old child so that it can influence the meaning of the words  semantically. The results obtained indicated that language acquisition of child aged 3 years old was still in the process of development language that will become perfect as them get older. There are 14 words that were not appropriate semantically. Those words were often spoken by the child. The relation between semantics and language acquisition of 3 years old child were assessed still in the development stage according to her age.  Keywords: Language Acquisition; linguistics, Semantics; language development of three years old child